Risk Management in Managerial Control of Local Self-Government Entities - Lomott, Marietta Janowicz; Åyskawa, Krzysztof (Richtmann Publishing, 2012)
Local government is now one of the most important political institutions of modern states including Poland. It is confirmed byboth of the Worldwide Declaration of Local Self-Government and the European Charter of Local Self-Government. It sometimes is evenrecognized as the fourth power in the country, next to the three powers of Montesquieu's classification. Local government units (JST inPolish) carry out their activities in accordance with the regulations contained in the legislation. There are set of tasks and tools that couldbe used. It should be noted that purpose of any organization and business activity, including local government, is to achieve its taskaccomplished and to preserve the possibility of further operation. The achieving of goals may be affected by circumstances arising fromthe action of external forces (strategic risk) or binding with the specificity of local government units (operational risk). An essentialelement in the functioning of local governments has become a risk management. This area became part of the internal managementcontrol processes in Poland and it should be implemented in any unit. However, in many cases, risk management comes down to controlthe correctness of implementation a few procedures. In the end, it does not control the effects of adverse events that occur in thefunctioning of local government units actually. It becomes necessary to indicate the direction of constructing such a risk managementprocedures to make them similar to actions are taken in enterprises..